Eighteenth-century English ideology and change - Hickey, Raymond 1954- (Studies in English language, 2014)
"The eighteenth century was a key period in the development of the English language, in which the modern standard emerged and many dictionaries and grammars first appeared. This book is divided into thematic sections which deal with issues central to English in the eighteenth century. These include linguistic ideology and the grammatical tradition, the contribution of women to the writing of grammars, the interactions of writers at this time and how politeness was encoded in language, including that on a regional level. The contributions also discuss how language was seen and discussed in public and how grammarians, lexicographers, journalists, pamphleteers and publishers judged on-going change. The novel insights offered in this book extend our knowledge of the English language at the onset of the modern period."--Provided by publisher.